ANALISIS FAKTOR YANG MEMPENGARUHI CAPITAL BUFFER PERBANKAN DI INDONESIA (STUDI PADA BANK-BANK KONVENSIONAL GO PUBLIC PERIODE 2010-2013) - Bayuseno, Vaditra; Chabahib, Mochammad (Diponegoro Journal of Management, 2014)
Capital buffer is the difference between the ratio of bank capital to the minimum capitaladequacy ratio of the central bank imposed. Capital buffer can be used by banks as capital reserve in the event of a variety of adverse economic shocks. Committee of international banks (Basel Committee on Banking Supervision) applying Basel Accord which requires each bank has capital reserve (CAR) by 13% in order to strenghten its capital position, reduce inequality over the different regulations in each country and consider the various risk banks in order to realize a soundness and stability of international banking.Banks in Indonesia during the period 2010-2013 have an average CAR of 17,56% which means that above the requirements have been imposed. CAR is too high is not too good for the banks because the capital can be used for development and profit. This study uses variables such as ROEt-1, NPLt-1, Lag of capital buffer (BUFFt-1), Loans to Total Assets (VLOAN) and Bank’s Share Assets (BSA) in analyzing the factors that determine the capital buffer of banks in Indonesia during the period 2010-2013. Moreover, there are gaps results of research conducted by previous researchers about the factors that determine the capital buffer.The results of this study showed capital buffer significantly affected by ROEt-1, Lag of capital buffer (BUFFt-1) and Bank’s Share Assets (BSA). The study found a significant poisitive correlation between ROEt-1 and Lag of capital buffer (BUFFt-1) to capital buffer. This is consistent wiith The Pecking Order Theory in which the banks can raise capital with retained earnings. In addition, this study also found negative correlation between BSA and capital buffer, so this finding is supporting Too Big Too Fail that state the larger banks tend to maintain their capital buffer lower than small banks.